Support-free iridium hydroxide for high-efficiency proton-exchange membrane water electrolysis - Yubo Chen; Chencheng Dai; Qian Wu; Haiyan Li; Shibo Xi; Justin Zhu Yeow Seow; Songzhu Luo; Fanxu Meng; Yaolong Bo; Yanghong Xia; Yansong Jia; Adrian C. Fisher; et al. (Nature Communications, 2025)
Abstract The large-scale implementation of proton-exchange membrane water electrolyzers relies on high-performance membrane-electrode assemblies that use minimal iridium (Ir). In this study, we present a support-free Ir catalyst developed through a metal-oxide-based molecular self-assembly strategy. The unique self-assembly of densely isolated single IrO6H8 octahedra leads to the formation of μm-sized hierarchically porous Ir hydroxide particles. The support-free Ir catalyst exhibits a high turnover frequency of 5.31 s⁻¹ at 1.52 V in the membrane-electrode assembly. In the corresponding proton-exchange membrane water electrolyzer, notable performance with a cell voltage of less than 1.75 V at 4.0 A cm⁻² (Ir loading of 0.375 mg cm⁻²) is achieved. This metal-oxide-based molecular self-assembly strategy may provide a general approach for the development of advanced support-free catalysts for high-performance membrane-electrode assemblies.